5.4k views
5 votes
Guys please help plsssssssss

Guys please help plsssssssss-example-1
User Shoreki
by
4.8k points

1 Answer

3 votes

Answer:

b = 15

Explanation:


(5\left((b-1)/(2)-1\right)+2b)/(3)\\5\left((b-1)/(2)-1\right)+2b\\5\left((b-1)/(2)-1\right)\\5\cdot (b-1)/(2)-5\cdot \:1\\5\cdot (b-1)/(2)\\(\left(b-1\right)\cdot \:5)/(2)\\(5b-5)/(2)\\(5b-5)/(2)-5\\(5b-5)/(2)-5+2b\\=(5b-5)/(2)+(2b\cdot \:2)/(2)\\=(5b-5+2b\cdot \:2)/(2)\\5b-5+4b\\5b+4b-5\\9b-5\\(9b-5)/(2)\\=(9b-5)/(2)-5\\=((9b-5)/(2)-5)/(3)\\(9b-5)/(2)-5\\(9b-5)/(2)-(5\cdot \:2)/(2)\\


=(9b-5-5\cdot \:2)/(2)\\9b-5-5\cdot \:2\\9b-5-10\\9b-15\\=(9b-15)/(2)\\=((9b-15)/(2))/(3)\\=(9b-15)/(2\cdot \:3)\\=(9b-15)/(6)\\(3\left(3b-5\right))/(6)\\(3b-5)/(2)\\=(3b)/(2)-(5)/(2)\\(3b)/(2)-(5)/(2)=5+b\\=(3b)/(2)\cdot \:2-(5)/(2)\cdot \:2=5\cdot \:2+b\cdot \:2\\(3b)/(2)\cdot \:2\\(3b\cdot \:2)/(2)\\=3b\\-(5)/(2)\cdot \:2\\=(5)/(2)\cdot (2)/(1)\\=-(5)/(1)\\=-5\\5\cdot \:2\\=10\\=3b-5=10+b\cdot \:2


\mathrm{Add\:5--both\:\:sides\:of\:the\:expression}\\3b-5+5=10+b\cdot \:2+5\\3b=2b+15\\\mathrm{Subtract}\\3b-2b=2b+15-2b\\\mathrm{Thus,}\\b=15

Hope it helps. :-)

User Uncle Iroh
by
5.4k points